A preparation method of MoCoB-based cermet
By using cobalt boride powder and molybdenum powder for wet grinding and rotary evaporator drying, the problems of long preparation time and degradation of MoCoB-based metal cermets are solved, and the process cycle is significantly shortened and the material performance is improved.
Patent Information
- Application Number
- CN202211496634.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-25
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-11-25
AI Technical Summary
The existing MoCoB-based cermet preparation process has a long cycle and a decrease in material performance after shortening the preparation time, especially the long ball milling and drying time caused by poor raw material density and segregation of mixed powder components.
Cobalt boride powder and molybdenum powder are used as raw materials, ball milling is carried out through a wet grinding process and dried in a rotary evaporator, which reduces the process time, improves the density uniformity and component distribution of the powder, and improves the preparation efficiency.
The preparation period is shortened by about 76.9% to 94.2%, the density and mechanical properties of MoCoB-based cermet are improved, and its hardness and bending strength are significantly improved.
Smart Images

Figure CN115821095B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation process of MoCoB-based metal ceramics, and belongs to the field of structural functional materials. Background Art
[0002] Boride-based cermets have the advantages of high hardness, good wear resistance, strong corrosion resistance of ceramics and high strength and good plasticity and toughness of metals, and are widely used in the fields of cutting tools, molds, etc. Among them, MoCoB-based cermets are new ternary boride-based cermets developed in recent years. They are composed of MoCoB hard phase and Co bonding phase, and have the advantages of high hardness, excellent wear resistance and strong high-temperature oxidation resistance. Compared with WCoB-Co cermets and WC-Co cermets, their raw materials do not contain the strategic scarce resource W element. Therefore, they have great potential in the field of wear-resistant materials.
[0003] The MoCoB hard phase is the boride with the highest theoretical hardness among the known ternary boride hard phases. The MoCoB-based cermets prepared by the existing process have good comprehensive mechanical properties and can meet conventional service conditions as wear-resistant materials. However, in the face of harsh working conditions such as chemical smelting, marine exploration, and oil extraction, its mechanical properties need to be further improved. In addition, the existing preparation process cycle is relatively long. The process flow of MoCoB-based cermets can be summarized as: batching → mixing → drying → molding → sintering → sintered body. There are many preparation steps. Among them, the three steps of mixing, drying and sintering take longer time than the other steps. With the development of new technologies such as self-propagating sintering and spark plasma sintering, the time required for sintering has been greatly reduced. However, the mixing and drying steps still take a long time. For example:
[0004] In the patent "A Carbon Fiber Reinforced MoCoB Metal Ceramics and Preparation Method" [ZL 202110663350.6], the ball milling process takes 10 to 24 hours and the drying process takes 8 to 10 hours, which seriously prolongs the preparation cycle and limits its industrial development. Therefore, if a new process can be found that can not only shorten the preparation cycle of MoCoB-based metal ceramics but also improve their mechanical properties, it can obviously accelerate their application and promotion in industry.
[0005] The patent "A Molybdenum-Cobalt-Boron Ternary Boride-Based Metal Ceramic Material and Its Preparation Method" [ZL 201711065933.9] uses elemental molybdenum powder, cobalt powder and boron powder as raw materials, and mentions that dry grinding can be used to ball-mill the mixed powder, thereby eliminating the drying process and saving time. However, since no liquid is added as the ball-milling medium, the degree of oxidation of the powder during the ball-milling process and the degree of agglomeration of the powder will increase, resulting in phenomena such as powder sticking to the wall and the ball, causing raw material loss. In addition, dry grinding will also aggravate the component segregation of the material, resulting in a decrease in the density of the metal ceramic, thereby causing a decrease in its mechanical properties. Its hardness is 83.5~85.0HRA, which is relatively low.
[0006] In summary, the existing MoCoB-based cermets have the problem of long preparation time and decreased material performance under the premise of shortened preparation time. Summary of the invention
[0007] In view of the defects or shortcomings of the prior art, the present invention provides a method for preparing a MoCoB-based cermet.
[0008] To this end, the preparation method provided by the present invention comprises: using cobalt boride powder and molybdenum powder as raw materials, firstly ball milling by wet grinding, then drying in a rotary evaporator, and then sintering in a spark plasma sintering furnace;
[0009] In terms of mass percentage, the cobalt boride powder is 45% to 63.0%, and the molybdenum powder is 37.0% to 55.0%;
[0010] The ball milling is carried out in an inert gas atmosphere, and the ball milling process control agent is one of ethyl acetate, anhydrous ethanol and acetone.
[0011] Optionally, in terms of mass percentage, the ball-to-material ratio in the ball milling process is 5:1 to 15:1, the rotation speed is 100 to 300 r / min, the ball milling time is 1 to 4 hours, and the inert gas in the ball milling process is one of nitrogen or argon.
[0012] Alternatively, the drying process parameters are: a temperature of 35 to 85°C, a rotation speed of 30 to 80 r / min, and a vacuum degree of 10 -2 ~10 -1 The drying process is carried out under the conditions of Pa; the drying time is 0.5 to 2 hours.
[0013] Furthermore, the MoCoB-based cermet comprises a MoCoB hard phase and a Co binder phase. The density of the MoCoB-based cermet is 98.34% to 98.81%. The hardness of the MoCoB-based cermet is 88.4 to 89.1 HRA, and the bending strength is 1621.8 to 1768.3 MPa.
[0014] The main raw materials used in the current preparation process are simple Mo powder, Co powder and B powder. Among them, the density of B powder is much smaller than that of Mo powder and Co powder. During ball milling, B powder will "float" in the upper space of the ball mill, and the grinding balls can hardly catch it. The ball milling efficiency is extremely low, which greatly increases the ball milling time. In addition, due to the density difference between the raw materials, it is difficult for the mixed powder to achieve a completely uniform distribution state. There will be a certain component segregation, resulting in uneven distribution of the microstructure of the sintered body, which is not conducive to improving its mechanical properties. In addition, the drying process in the existing conventional preparation method is limited by the density difference in the three-component mixed powder and the low density characteristics of B powder. Usually, a vacuum drying oven with extremely low efficiency is used for static drying, which greatly prolongs the preparation cycle. To address this problem, the inventors conducted in-depth research and found that binary borides (cobalt boride or molybdenum boride) can be used instead of B powder. By adjusting the composition ratio of the binary boride, only two components of raw materials, namely binary boride and metal powder, can be used. At the same time, wet grinding process and rotary evaporator are used for drying, which can not only solve the problems of long ball milling and drying process time and segregation of mixed powder components caused by the difference in raw material powder density, but also shorten the processing time and ensure that the performance of the processed material is better.
[0015] Compared with the prior art, the present invention uses cobalt boride powder and molybdenum powder as raw materials, and adopts wet ball milling and rotary evaporator drying processes, thereby improving the preparation efficiency and shortening the preparation cycle by about 76.9% to 94.2%; at the same time, it also improves the problem of segregation of mixed powder components, and prepares MoCoB-based cermets with denser microstructure and good comprehensive mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is the XRD spectrum of the MoCoB-based cermet in Example 2 of the present invention;
[0017] Figure 2 This is a fracture morphology photograph of the MoCoB-based cermet in Example 2 of the present invention;
[0018] Figure 3 This is a fracture morphology photograph of the MoCoB-based cermet in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0019] Unless otherwise specified, the scientific and technological terms and methods herein are understood according to the knowledge of ordinary technicians in the relevant field or implemented using existing relevant methods. It should also be understood that the temperature and process duration involved in this article are approximate values for illustrative purposes. Although methods and materials similar or equivalent to the methods and materials described herein can be used for the implementation of the present disclosure, some suitable methods and materials are described below. The publications, patent applications, patents and other references mentioned herein are partially incorporated herein by reference. If there is a conflict, this article shall prevail. In addition, the materials, methods, material ratios and embodiments are only exemplary and are not intended to be limited. In the specific scheme, those skilled in the art can use conventional experimental time periods to optimize the material ratios and operating parameter values involved in the method according to the disclosure of the present invention to achieve the purpose of the present invention.
[0020] In the process of the present invention, a rotary evaporator is used for drying. Based on the disclosure of the present invention, those skilled in the art can use conventional experimental means to optimize the specific drying process according to different formula materials and the effects of the present invention. The specific drying process adopted in the following embodiments is only a specific example to explain the scheme of the present invention, and the drying process of the present invention is not limited to this. The drying process parameter example is at a temperature of 35 to 85°C, a rotation speed of 30 to 80 r / min, and a vacuum degree of 10 -2 ~10 -1 The drying process is carried out under the conditions of Pa; the drying time is 0.5 to 2 hours.
[0021] In the process of the present invention, a spark plasma sintering furnace is used for sintering. Based on the disclosure of the present invention, those skilled in the art can use conventional experimental means to optimize the specific sintering according to different formula materials and the effects of the present invention. The specific sintering process adopted in the following embodiments is only a specific example to explain the scheme of the present invention, and the sintering process of the present invention is not limited to this.
[0022] The present invention is further described in detail below by way of examples. The raw materials cobalt boride powder and molybdenum powder used in the examples of the present invention are both commercially available chemically pure powder reagents.
[0023] The present invention adopts the Archimedes drainage method to test the density of the MoCoB-based cermet; uses the HRS-150 Rockwell hardness tester to measure the hardness of the MoCoB-based cermet; and refers to the national standard GB / T6569-2006 and adopts the three-point bending test method to test the flexural strength of the MoCoB-based cermet sample.
[0024] Embodiment 1:
[0025] This embodiment uses cobalt boride powder and molybdenum powder with a purity of not less than 99.0% as raw materials, and the mass percentage is: cobalt boride powder: 45.0%, molybdenum powder: 55.0%;
[0026] The ball milling was carried out by wet milling, with acetone as the ball milling medium, in a nitrogen atmosphere, with a ball-to-material ratio of 15:1, a rotation speed of 300 r / min, and a time of 1 h.
[0027] The milled slurry was then dried using a rotary evaporator at a temperature of 85°C and a vacuum of 10 -2 Pa, the rotation speed is 80r / min, and the drying time is 0.5h;
[0028] Then, the material is sintered in a spark plasma sintering furnace (sintering process parameters: heating rate 100°C / min, sintering temperature 1300°C, holding time 5min, pressure 50MPa) to obtain MoCoB-based metal ceramics.
[0029] In this embodiment, the time used for the ball milling and drying process is 1.5 hours. After testing, the microstructure and mechanical properties of the prepared MoCoB-based cermet are: density is 98.34%, hardness is 88.4HRA, and flexural strength is 1621.8MPa.
[0030] Embodiment 2:
[0031] This embodiment uses cobalt boride powder and molybdenum powder with a purity of not less than 99.0% as raw materials, and the mass percentage is: cobalt boride powder: 54.0%, molybdenum powder: 46.0%;
[0032] The ball milling was carried out by wet milling, the ball milling medium was ethyl acetate, the ball milling was carried out in an argon atmosphere, the ball-to-material ratio was 10:1, the rotation speed was 200 r / min, and the time was 2 h;
[0033] The milled slurry was then dried using a rotary evaporator at a temperature of 60°C and a vacuum of 10 -2 Pa, the rotation speed is 60r / min, and the drying time is 1h;
[0034] Then, the material is sintered in a spark plasma sintering furnace (sintering process parameters: heating rate 100°C / min, sintering temperature 1300°C, holding time 5min, pressure 50MPa) to obtain MoCoB-based metal ceramics.
[0035] The ball milling and drying process in this embodiment takes 3.0 h. After testing, the prepared MoCoB-based cermet contains MoCoB hard phase and Co binder phase (see XRD spectrum). Figure 1 ), microstructure see Figure 2; The mechanical properties are: density is 98.81%, hardness is 89.1HRA, and flexural strength is 1768.3MPa.
[0036] Embodiment 3:
[0037] This embodiment uses cobalt boride powder and molybdenum powder with a purity of not less than 99.0% as raw materials, and the mass percentage is: cobalt boride powder: 63.0%, molybdenum powder: 37.0%;
[0038] The ball milling was carried out by wet milling, with acetone as the ball milling medium, in a nitrogen atmosphere, with a ball-to-material ratio of 5:1, a rotation speed of 100 r / min, and a time of 4 h.
[0039] The milled slurry was then dried using a rotary evaporator at a temperature of 35°C and a vacuum of 10. -1 Pa, the rotation speed is 30r / min, and the drying time is 2h;
[0040] Then, the material is sintered in a spark plasma sintering furnace (sintering process parameters: heating rate 100°C / min, sintering temperature 1300°C, holding time 5min, pressure 50MPa) to obtain MoCoB-based metal ceramics.
[0041] In this embodiment, the time taken for the ball milling and drying process is 6.0 hours. After testing, the microstructure and mechanical properties of the prepared MoCoB-based metal ceramic are as follows: density is 98.58%, hardness is 88.8HRA, and bending strength is 1672.3MPa. Comparative Example 1:
[0042] This comparative example uses Mo, Co and B powders with a purity of not less than 99.0% as raw materials, and the weight percentages are: Mo: 46.0%, Co: 49.0%, B: 5.0%. Other than that, the preparation process is completely consistent with Example 2.
[0043] Since the powder obtained after ball milling and drying has great component segregation, the obtained sintered body has poor density and is extremely brittle.
[0044] Comparative Example 2:
[0045] Comparative Example 2 adopts the same preparation process as Example 2, except that a dry grinding ball milling method is adopted. The specific process is as follows: cobalt boride powder and molybdenum powder with a purity of not less than 99.0% are used as raw materials, and the weight percentage is: cobalt boride powder: 54.0%, molybdenum powder: 46.0%;
[0046] The ball milling was carried out by dry milling in an argon atmosphere with a ball-to-material ratio of 10:1, a rotation speed of 200 r / min, and a time of 2 h.
[0047] Then, the sintering is carried out in a spark plasma sintering furnace (sintering process parameters: heating rate 100°C / min, sintering temperature 1300°C, holding time 5min, pressure 50MPa).
[0048] In this comparative example, since the powder after dry grinding has obvious agglomeration, component segregation and oxidation, the obtained sintered body has poor density and extremely great brittleness.
[0049] Comparative Example 3:
[0050] This comparative example uses Mo, Co and B powders with a purity of not less than 99.0% as raw materials, and prepares MoCoB-based metal ceramics in the following weight percentages: Mo: 46.0%, Co: 49.0%, and B: 5.0%; in order to improve the performance of the MoCoB-based metal ceramics, after optimization, the process adopted in this comparative example is: the ball milling time is 16 hours, and the drying is carried out in a vacuum drying oven for 10 hours, and the remaining processes are the same as those in Example 2.
[0051] The time taken for the ball milling and drying process of this comparative example is 26.0 h, and the obtained MoCoB-based metal ceramic microstructure (see Figure 3 ) and mechanical properties are: density is 97.25%, hardness is 87.8HRA, and flexural strength is 1534.2MPa.
[0052] The preparation process cycles and test performances of the MoCoB-based cermets of the above-mentioned embodiments and comparative examples are summarized in Table 1.
[0053] Table 1 Preparation process cycle, microstructure and mechanical properties of MoCoB-based cermets
[0054]
[0055]
[0056] from Figure 2 and Figure 3 It can be seen from the fracture morphology of the MoCoB-based metal ceramics that, compared with the existing conventional preparation process, the number of pores in the MoCoB-based metal ceramics prepared by using two-component raw materials and optimized ball milling and drying processes is reduced, indicating that the density is further improved. At the same time, the number of transgranular fractures increases, which will consume more energy when bearing and improve the bending strength of the metal ceramics.
[0057] It can be seen from the test results in Table 1 that, compared with Comparative Example 3, the present invention uses two-component raw materials and optimized ball milling and drying processes to prepare MoCoB-based metal ceramics, which significantly reduces the working hours by about 76.9% to 94.2%; the density of the prepared MoCoB-based metal ceramics is increased, and the hardness and flexural strength are increased, and the comprehensive mechanical properties are improved.
Claims
1. A method for preparing a MoCoB-based cermet, It is characterized in that The preparation method comprises: using cobalt boride powder and molybdenum powder as raw materials, firstly ball milling by wet milling, then drying in a rotary evaporator, and then sintering in a spark plasma sintering furnace; In terms of mass percentage, the cobalt boride powder is 45% to 63.0%, and the molybdenum powder is 37.0% to 55.0%; The ball milling is carried out in an inert gas atmosphere, and the ball milling process control agent is one of ethyl acetate, anhydrous ethanol and acetone; the ball-to-material ratio in the ball milling process is 5:1-15:1, the rotation speed is 100-300r / min; the ball milling time is 1-4h; the drying temperature is 35-85°C, the rotation speed is 30-80r / min, and the vacuum degree is 10 -2 ~10 -1 Pa; drying time is 0.5 to 2 hours; The density of the MoCoB-based cermet is 98.34% to 98.81%, the hardness of the MoCoB-based cermet is 88.4 to 89.1 HRA, and the flexural strength is 1621.8 to 1768.3 MPa; The MoCoB-based cermet comprises a MoCoB hard phase and a Co binder phase.
2. The method for preparing the MoCoB-based cermet according to claim 1, It is characterized in that The inert gas during ball milling is either nitrogen or argon.
